2018
DOI: 10.1140/epjd/e2018-90522-y
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quantumness: from theory to observability in interferometric setups

Abstract: We investigate the notion of quantumness based on the non-commutativity of the algebra of observables and introduce a measure of quantumness based on the mutual incompatibility of quantum states. We show that such a quantity can be experimentally measured with an interferometric setup and that, when an arbitrary bipartition of a given composite system is introduced, it detects the one-way quantum correlations restricted to one of the two subsystems. We finally show that, by combining only two projective measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The nonclassicality of quantum systems can be conveniently quantified using the Hilbert-Schmidt norm of the commutator of two states, which is proposed to witness the “state incompatibility” between any two admissible states ρ a and ρ b 3940. The “quantumness” is then defined as…”
Section: Quantum Speed Limit To the Dynamics Of Quantumnessmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonclassicality of quantum systems can be conveniently quantified using the Hilbert-Schmidt norm of the commutator of two states, which is proposed to witness the “state incompatibility” between any two admissible states ρ a and ρ b 3940. The “quantumness” is then defined as…”
Section: Quantum Speed Limit To the Dynamics Of Quantumnessmentioning
confidence: 99%
“…and Q(ρ a , ρ b ) = 0 iff [ ρ a , ρ b ] = 03940. Choosing ρ a  =  ρ 0 and ρ b  =  ρ t , Q (ρ 0 , ρ t ) allows one to quantify the capacity of an arbitrary physical process to generate or sustain quantumness in case of [ ρ 0 , ρ t ] ≠ 0.…”
Section: Quantum Speed Limit To the Dynamics Of Quantumnessmentioning
confidence: 99%
See 1 more Smart Citation
“…is the Bessel function of second order. This formula is valid for ω ≥ The problem with coherent states is that a beam splitter cannot change the entanglement degree of any state codified in them [21], so the dynamics is essentially classical [23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Quantum generalization of the Fisher information has also been introduced [45,46], which can be considered as a measure of non-classicality for quantum system [47,48]. A measure of quantumness has been proposed in a recent work [49], based on the non-commutativity of quantum states. We have shown that the Quantum Fisher information is lower bounded by the above mentioned quantumness with a factor of 1/4 and upper bounded by the l 1 norm of coherence with a factor of 1/2.…”
Section: Introductionmentioning
confidence: 99%